2014
DOI: 10.1177/0268355514555386
|View full text |Cite
|
Sign up to set email alerts
|

Maggots as a wound debridement agent for chronic venous leg ulcers under graduated compression bandages: A randomised controlled trial

Abstract: Larval debridement therapy improves wound debridement in chronic venous leg ulcers treated with multilayer compression bandages. However, no subsequent improvement in ulcer healing was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 15 publications
(20 reference statements)
0
28
0
Order By: Relevance
“…Among these 16 studies, 12 identified that having defined a set of "too restrictive" selection criteria was a major issue, which led to a lack of eligible patients. [11][12][13][14]17,19,23,24,27,30,33,35 To improve recruitment, 3 studies amended the participant selection criteria. 10,23,35 Seven studies reported that fewer patients were eligible, 10,14,15,18,27,30,34 even when on-site clinicians were consulted during study conception.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among these 16 studies, 12 identified that having defined a set of "too restrictive" selection criteria was a major issue, which led to a lack of eligible patients. [11][12][13][14]17,19,23,24,27,30,33,35 To improve recruitment, 3 studies amended the participant selection criteria. 10,23,35 Seven studies reported that fewer patients were eligible, 10,14,15,18,27,30,34 even when on-site clinicians were consulted during study conception.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Characteristics of included studies are presented in Table 2. Studies were conducted in the United Kingdom (n = 12, 44.4%) 10,11,14,15,19,[25][26][27]30,31,33,34 ; Australia (n = 4, 14.8%) 17,23,28,29 ; the United States (n = 2, 7.4%) 12,36 ; and 1 each from Canada (3.7%), 35 Germany (3.7%), 18 India (3.7%), 20 Italy (3.7%), 32 Mexico (3.7%), 22 and New Zealand (3.7%). 21 The remaining 3 studies (11.1%) were conducted in more than 1 country: the United States and Canada 13 or the United Kingdom 24 and the European Union and Australia.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations